Medicinal psychedelics for mental health and addiction: Advancing research of an emerging paradigm. (December 2021) - Perkins, Daniel; Sarris, Jerome; Rossell, Susan; Bonomo, Yvonne; Forbes, David; Davey, Christopher; Hoyer, Daniel; Loo, Colleen; Murray, Greg; Hood, Sean; Schubert, Violeta; Galvão-Coelho, Nicole Leite; et al.
The medical use of psychedelic substances (e.g. psilocybin, ayahuasca, lysergic acid diethylamide and 3, 4-methylenedioxymethamphetamine) is attracting renewed interest, driven by a pressing need for research and development of novel therapies for psychiatric disorders, as well as promising results of contemporary studies. In this Viewpoint, we reflect upon the 'Clinical Memorandum on Psychedelics' recently released by the Royal Australian and New Zealand College of Psychiatrists and note subsequent developments including the application for down-scheduling of psilocybin and 3, 4-methylenedioxymethamphetamine presently being considered by the Therapeutic Goods Administration and approvals for access via the Special Access Scheme. We suggest that this field is worthy of rigorous research to assess potential benefits, address safety parameters and clarify therapeutic mechanisms. To this end, we outline recent research findings, provide an overview of current knowledge relating to mechanisms of action and discuss salient aspects of the psychedelic-assisted psychotherapy treatment model. The sum of this research points towards medicinal psychedelics as a potential new class of psychiatric treatments when used within a medically supervised framework with integrated psychotherapeutic support. However, before widespread translation into clinical use can occur, appropriately designed and sufficiently powered trials are required to detect both potential positive and negative outcomes. Unique safety and regulatory challenges also need to be addressed. As for any new medical therapy, psychedelic research needs to be conducted in a rigorous manner, through the dispassionate lens of scientific enquiry. Carte blanche availability to practitioners, without specific protocols and appropriate training, would be potentially harmful to individuals and detrimental to the field.